Knowledge and practices concerning the effects of ionizing radiation and x-ray protection methods in dental offices in Babol, 2013 - Gholamreza Ataei; Sina Haghanifar; Masomeh karimi; Fereshteh Adel (Babol University of Medical Sciences, 2015)
Introduction: As the absorption of radiation in environment is increasing, the present study was performed to evaluate the knowledge and practices of Babol’s dentists about x-ray protection . Materials &Methods: This cross-sectional study was designed to assess the knowledge and practices of dentists. The questionnaires were distributed among 70 dentists in Babol city. Analysis of the collected data was done using the Pearson correlation coefficient in SPSS software version 19 (α=0.05). Results: In this study, 70% and 30% of studied dentists had good and moderate knowledge, respectively. 96% of them were moderate in terms of practice and 70% of them had good awareness towards the use of a lead apron and thyroid collar but 78.6% and 75.7% of offices had no lead apron and thyroid collar. There was a significant relationship between experience and awareness (p=0.003). Conclusion: According to the results, their appropriate knowledge and practice were poor. Therefore, it is necessary to control the dental radiographic centers.